Influence of key parameters of ice accretion model under coexisting rain and fog weather - Zhou, Yue; Wan, Rong; Sun, Jing; Gao, Zhengxu; Yang, Jialun (Frontiers in Earth Science, 2023)
Based on 30 complete wire icing processes lasted longer than 24 h observed from the Enshi, Jinsha, Dacaoping and Shennongding of Shennongjia in mountainous areas of Hubei province during the winter of 2008–2016, the macroscopic effects of rain–fog weather on the ice accretion process were analyzed. Furthermore, the distribution characteristics of key simulation parameters in supercooled fog (SF) and freezing rain (FR) were discussed according to the physical model of icing process. Finally, the evolution characteristics of the simulated ice thickness in rain–fog weather were proposed. Results showed that the duration of ice accretion in mountainous areas is the key factor affecting the maximum ice thickness; the freezing rain is most frequent during the glaze icing process, which leads to the substantial growth of ice thickness. The average growth rates of ice thickness with and without freezing rain are 1.26 mm h−1 and -0.11 mm h−1, respectively. Collision rate is the main parameter for inhibiting ice accretion of SF, with an average value of ~ 0.1, while freezing rate is the main parameter for inhibiting ice accretion of FR, with an average value of ~ 0.6. The ice accretion of SF shows the characteristics of periodic growth, while the ice accretion of FR shows the explosive growth of ice thickness, which makes the simulated values of icing closer to the observations. The ice formation efficiency of FR was more than twice that of SF, with a negative feedback mechanism to the ice accumulation of SF.